Early-Life Exposure to Malnutrition From the Chinese Famine on Risk of Asthma and Chronic Obstructive Pulmonary Disease in Adulthood - Jin, Changbo; Zhang, Tiantian; Li, Yongzhen; Shi, Wenming (Frontiers in Nutrition, 2022)
Objectives: Intrauterine malnutrition has a long-term effect on respiratory and lung function. However, few studies have explored the association between early-life exposure to famine with asthma and chronic obstructive pulmonary disease (COPD) in adulthood. Therefore, we aimed to investigate the association of early-life exposure to the Chinese famine of 1959–1962 with asthma and COPD later in life. Methods: This national population-based study included 6,771 participants from the baseline survey of the China Health and Retirement Longitudinal Study (CHARLS) who were born around the time of the Chinese famine. The famine exposure groups were determined according to the participants’ birth year as non-exposed (1964–1967), fetal-exposed (1959–1962), preschool-exposed (1954–1957) and school-age exposed (1950–1953). Information about the demographic characteristics, self-reported doctor-diagnosed asthma and COPD, behaviour and lifestyles, and indoor pollution were collected using validated questionnaires. In addition, peak expiratory flow (PEF) was measured to assess pulmonary function. Multivariable logistic regression and generalized linear mixed models were performed to explore the risk of adult asthma and COPD, PEF changes during various famine exposure periods compared with the non-exposed group. Stratified and sensitivity analyses were conducted to examine the modification and robustness of the association. Results: The prevalence of doctor-diagnosed asthma and COPD was 2.8% and 8.1%, respectively. Compared with the non-exposed group, the risk was significantly higher in the fetal-exposed group for asthma (adjusted odds ratio, [aOR]=1.87, 95% confidence interval [CI]:1.14–3.07) and the school-age exposed group [1.30 (1.00–1.69)] for COPD after controlling for confounders. Furthermore, we observed that fetal exposure to famine was significantly associated with a decrement of PEF in adulthood (β= -11.38 [-22.75 to -0.02]) compared with the non-exposed group. Stratified analyses showed that the association of asthma was stronger in males, who resided in severely famine-affected areas, smoked, and used solid fuels for cooking. No clearly consistent association was observed for subsequent COPD. Conclusions: Our results suggest that fetal exposure to the Chinese famine is significantly associated with the increased risk of asthma in adulthood. Future prospective studies are warranted to examine the association and mechanisms.